Football referees issue more yellow cards following VAR interventions - mental, tactical, and performance considerations - Roy, D. S.; Galily, Y.; Englert, C.; Basevitch, I. (International Journal of Sports Science & Coaching, 2025)
VAR (video assistant referee) presents a human-technology interface that was designed to improve referees` ability to make accurate decisions in key match incidents. VAR interventions are pivotal moments in football matches, challenging referees` critical decisions and potentially affecting their perceived ability to manage the game. This study aimed to investigate how referees handle VAR interventions in terms of game management and control. Through statistical analyses, we examined 120 real-match VAR interventions in penalty incidents from the Israeli Premier League, focusing on the number of fouls and yellow cards before and after the VAR interventions. Our findings revealed a significant impact (d = 0.40) on yellow cards but not on fouls. Remarkably, referees issued twice the number of yellow cards (normalized per playing minute) following a VAR intervention, irrespective of the time it occurred during the match (i.e., first or second half). These results are discussed within the framework of current research and theories concerning self-control and game management in football refereeing. The increased issuance of yellow cards following VAR interventions suggests that teams may be at a higher risk of receiving disciplinary actions, which can potentially impact their performance and increase the likelihood of losing matches. Consequently, we provide practical recommendations for referee training and match preparation as well as for teams.